THE ROLE OF AUGMENTED REALITY TECHNOLOGY IN AGRICULTURAL TRAINING AND EXTENSION IN TURKEY - Lukas Schneider; Lena Wagner; Carloz Perez (Techno Agriculturae Studium of Research, 2025)
This study examines the role of augmented reality (AR) technology in agricultural training and extension in Turkey. The background of the research is based on the need to improve the effectiveness of training for farmers in understanding and applying modern agricultural techniques. The purpose of this study is to explore the impact of the use of AR on the improvement of farmers' knowledge and skills as well as the adoption of agricultural technology. This study uses a qualitative approach through surveys, interviews, and case studies in the Aegean region, involving 50 farmers and agricultural extension workers. The results showed that 75% of farmers experienced increased understanding, while 60% felt more confident in applying the techniques learned. Case studies also show that AR helps visualize irrigation techniques more clearly, making it easier for farmers to make decisions. The conclusion of this study is that AR makes a significant contribution in improving the quality of agricultural training, although limited access to technology is still a major obstacle. Further research is recommended to evaluate the long-term impact of AR on the productivity and efficiency of the agricultural sector in Turkey.